TREX-DM: a low background Micromegas-based TPC for low-mass WIMP detection. Issue 4 (May 2016) - Iguaz, F J; Garza, J G; Aznar, F; Castel, J F; Cebrián, S; Dafni, T; García, J A; Irastorza, I G; Lagraba, A; Luzón, G; Peiró, A
Abstract: Dark Matter experiments are recently focusing their detection techniques in low-mass WIMPs, which requires the use of light elements and low energy threshold. In this context, we describe the TREX-DM experiment, a low background Micromegas-based TPC for low-mass WIMP detection. Its main goal is the operation of an active detection mass ~0.3 kg, with an energy threshold below 0.4 keVee and fully built with previously selected radiopure materials. This work describes the commissioning of the actual setup situated in a laboratory on surface and the updates needed for a possible physics run at the Canfranc Underground Laboratory (LSC) in 2016. A preliminary background model of TREX-DM is also presented, based on a Geant4 simulation, the simulation of the detector's response and two discrimination methods: a conservative muon/electron and one based on a neutron source. Based on this background model, TREX-DM could be competitive in the search for low-mass WIMPs. In particular it could be sensitive, e.g., to the low-mass WIMP interpretation of the DAMA/LIBRA and other hints in a conservative scenario.